Anaesthesia for infant with Jarcho Levin syndrome: case report - Geze,Sukran (2015)
ABSTRACTJarcho Levin syndrome is a rare disorder. There are various vertebral and costal anomalies. Severe deformities and abnormal fusion of ribs and vertebrae cause respiratory insufficiency and pneumonia. We present anaesthesia in a patient with Jarcho Levin syndrome for vesicoureteral reflux.